Individual, organizational and social level antecedents of work-family enrichment: Does gender acts as a moderator?. Issue 1 (7th January 2019) - Mishra, Pavitra; Bhatnagar, Jyotsna
Abstract : Purpose: This study aims to fulfill the need to explore positive side of work–family interface, especially in emerging economies like India. The authors assessed the relationships of individual (family role salience), organizational (work–family culture) and social (community support) antecedents to work-to-family enrichment. They also examined whether gender moderated the relationship between the three antecedents and work-to-family enrichment. Design/methodology/approach: Data were collected on a questionnaire scale from 487 employees. Findings: It has been found that family role salience, supportive work-family culture and community support were directly related to work-to-family enrichment. Gender did not influence the relationship between work-family culture and work-to-family enrichment. However, relationships between family role salience and work-to-family enrichment, and between community support and work-to-family enrichment, were stronger in case of the male employees. The evolving nature of gender and integration of work-family-community domain provide insights into managers and policymakers about the importance of family and community in the organizations. Practical implications: The study builds a business case for facilitating a positive work-family culture in India for both male and female employees. The results point to the transitioning socio-cultural scenario of India, which advocates more similarities than differences in modern gender role expectations and identity. The current study emphasizes that while formulating policy, managers and policymakers should keep in mind evolving preferences of both the genders. Originality/value: The research provides a holistic view of how individual-, organizational- and social-level factors may affect employees' work–family enrichment in India. It also highlights the changing role of gender. Theoretical and practical limitations are also discussed.